Keanekaragaman Anggrek (Orchidaceae) di Taman Wisata Alam Sorong, Kota Sorong, Papua Barat - Reza Saputra; Djefry Tibalia; Fajar Darwis; Akbar Sumirto (Jurnal Biologi Papua, 2018)
Orchid diversity studies have been conducted at the Sorong Nature Park, Sorong City, West Papua. There are 84 collection numbers consisting of 69 epiphytic orchids, 14 terrestrial orchids, and 1 holomycotrophic orchid. This number belongs to 34 genera and 84 species, which are native species with at least 36 endemic species.  Dendrobium, Bulbophyllum, and Taeniophyllum are the three genera with the highest numbers of species. Key words: Orchid, Diversity, Sorong National Park, West Papua.